2020
DOI: 10.1177/0883911520960502
|View full text |Cite
|
Sign up to set email alerts
|

Tooth desensitizing calcium phosphate composite gelatin-based gel

Abstract: Dentine sensitivity is a dental problem common in individuals aged between 20 and 50 years. The most effective treatment method involves occluding the exposed dental tubules. This study focused on the synthesis of calcium phosphate nanoparticles in the form of gel to use as a proof of concept for home-treatment of sensitive teeth. In this study, calcium phosphate nanoparticles were prepared using emulsion method, in which oleic fatty acid was employed as an external phase, and sodium dodecyl sulphate (SDS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The ability of the gel to occlude dentine tubules was tested in vitro using human dentine slices with the dimension of 1×1×0.15 cm according to a previously reported method 19) . First, the dentine slices were sonicated for 15 min in ethanol to clean them and then air dried.…”
Section: Evaluation Of Dentinal Tubule Occlusion By the Tween80/ Calc...mentioning
confidence: 99%
“…The ability of the gel to occlude dentine tubules was tested in vitro using human dentine slices with the dimension of 1×1×0.15 cm according to a previously reported method 19) . First, the dentine slices were sonicated for 15 min in ethanol to clean them and then air dried.…”
Section: Evaluation Of Dentinal Tubule Occlusion By the Tween80/ Calc...mentioning
confidence: 99%
“…Yan et al [ 12 ] reported that the addition of graphene oxide to gelatin/polyacrylamide hydrogels significantly improved their mechanical properties, including elastic modulus and fractured stress. Waiyawat et al [ 13 ] developed a gelatin-based gel containing calcium phosphate nanoparticles for treating dentine sensitivity. Belonging to the category of bioceramics, calcium phosphates (CaPs) exhibit outstanding biological, physical, and chemical properties owing to their composition, closely resembling that of compounds found in teeth and bones [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%